Exploration of the genomic atlas of Dof transcription factor family across genus Oryza provides novel insights on rice breeding in changing climate - Tabassum, Javaria; Raza, Qasim; Riaz, Awais; Ahmad, Shakeel; Rashid, Muhammad Abdul Rehman; Javed, Muhammad Arshad; Ali, Zulfiqar; Kang, Fengyu; Khan, Iqrar Ahmad; Atif, Rana Muhammad; Luo, Ju (Frontiers in Plant Science, 2022)
DNA-binding with one finger (Dof) transcription factors have been demonstrated to regulate various stresses and developmental processes in plants. Their identification and comparative evolutionary analyses in cultivated and wild species of genus oryza were yet to be explored. In this context, we report a comprehensive genomics atlas of DNA-binding with one finger (Dof) family genes in 13 diverse rice genomes (five cultivated and eight rice wild-relatives) through a genome-wide scanning approach. A galore of 238 Dof genes, identified across the genus Oryza, are categorized into seven distinct subgroups by comparative phylogenetic analysis with the model plant Arabidopsis. Conserved motifs and gene structure analyses unveiled the prevalence of species- and subgroups-specific structural and functional diversity that is expediating with the evolutionary period. Our results indicate that Dof genes might have undergone strong purifying selections and segmental duplications to expand their gene family members in corresponding Oryza genomes. We speculate that miR2927 potentially targets the Dof domain to regulate gene expression under different climatic conditions, which are supported by in-silico and wet-lab experiments-based expression profiles. In a nutshell, we report several superior haplotypes significantly associated with early flowering in a treasure trove of 3,010 sequenced rice accessions and have validated these haplotypes with two years of field evaluation-based flowering data of a representative subpanel. Finally, we have provided some insights on the resolution of Oryza species phylogeny discordance and divergence highlighting the mosaic evolutionary history of the genus Oryza. Overall, this study reports a complete genomic landscape of the Dof family in cultivated and wild Oryza species that could greatly facilitate in fast-track development of early maturing and climate-resilient rice cultivars through modern haplotype-led breeding.